2020
DOI: 10.1108/hcs-02-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Extra care housing: exploring motivations, expectations and perceptions

Abstract: Purpose The purpose of this paper is to explore and compare the motivations and expectations that older people have when choosing to move into either a private or housing association (HA) extra care housing (ECH) scheme, and any effects this had on its residents. Design/methodology/approach This qualitative study is based on findings from four HA schemes in Tower Hamlets, London, and one private scheme in Warwickshire. Eight semi-structured interviews were conducted with five women and three men of varying b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…According to Gyasi (2020), this has had the potential of engendering intense anxiety, fear and exponential increase in death rates in Ghana. Notwithstanding that, government after government have made little effort in improving the lives of people through health, education, water and sanitation, energy and housing (Buckland and Tinker, 2020;Mallo and Hunt, 2014;Pittini, 2012). However, the proportions of each of these efforts differ significantly across cities and change over time as priorities and policies change.…”
Section: Introductionmentioning
confidence: 99%
“…According to Gyasi (2020), this has had the potential of engendering intense anxiety, fear and exponential increase in death rates in Ghana. Notwithstanding that, government after government have made little effort in improving the lives of people through health, education, water and sanitation, energy and housing (Buckland and Tinker, 2020;Mallo and Hunt, 2014;Pittini, 2012). However, the proportions of each of these efforts differ significantly across cities and change over time as priorities and policies change.…”
Section: Introductionmentioning
confidence: 99%
“…These participants were afraid of becoming a burden on family, so moved into AL SIH Koenig et al (2014). found that pull factors for moving into AL SIH included a secure environment, and availability of social activities and communal facilities Buckland and Tinker's (2020). study found that older people's decisions to move to AL SIH were often prompted by health deterioration, or sudden illness events, and for some older people, a consequent fear of being a burden on family.with a range of demographic, health and socioeconomic predictors.…”
mentioning
confidence: 99%